2019
DOI: 10.1108/jcp-05-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

What leads victims to resist? Factors that influence victim resistance in sexual assaults

Abstract: PurposeVictim resistance has been shown to have an important impact on the outcome of sexual assaults. Thus, the factors that affect a victim’s likelihood of various levels of resistance are relevant to consider, given the possibly detrimental effect these actions can have on crime outcome. While not intended to blame the victim in any way, it is important to examine the role the victim plays within a sexually coercive interchange in order to completely understand the sex crime event and, thus, be able to info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 58 publications
(99 reference statements)
0
9
2
Order By: Relevance
“…Similarly, the more severe the victim resistance, the more important the offender and crime context variables were. These findings are different from the study by Balemba and Beauregard (2019) which identified offender disinhibitor variables (i.e. sexual arousal, pornography prior to the crime) as the most predictive of victim resistance.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Similarly, the more severe the victim resistance, the more important the offender and crime context variables were. These findings are different from the study by Balemba and Beauregard (2019) which identified offender disinhibitor variables (i.e. sexual arousal, pornography prior to the crime) as the most predictive of victim resistance.…”
Section: Discussioncontrasting
confidence: 99%
“…They found that when offenders were intoxicated with alcohol and/or drugs, victims were more likely to use verbal or physical resistance (Atkeson et al, 1989). This result has been confirmed by more recent studies showing that offender intoxication led to an increase in the level of the victim's resistance (Balemba and Beauregard, 2019;Chopin and Beauregard, 2021;Clay-Warner, 2003).…”
Section: Literature Reviewmentioning
confidence: 74%
See 3 more Smart Citations